Математичне моделювання процесу накопичення метаноутворюючих мікроорганізмів в анаеробному біофільтрі - Скляр, Олександр Григорович; Скляр, Радміла Вікторівна; Болтянський, Борис Володимирович; Акулов, Вячеслав Дмитрович; Пушка, Олександр Сергійович; Skliar, Oleksandr; Skliar, Radmila; Boltianskyi, Borys; Akulov, Viacheslav; Pushka, Olexandr (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розроблено математичну модель процесу накопичення метаноутворюючих мікроорганізмів в анаеробному біофільтрі біогазової установки. Обґрунтовано кінетичні залежності, що описують вплив концентрації органічної речовини, дози завантаження метантенка та конструктивних параметрів носіїв на швидкість утворення біогазу. Модель побудована з використанням рівнянь Моно та враховує процес закріплення активної біомаси на поверхні носія. Запропонований підхід дозволяє інтенсифікувати анаеробне зброджування гнойових стоків і підвищити енергетичну ефективність біогазових установок. /// EN: The article presents the development and theoretical substantiation of a mathematical model describing the process of accumulation of methanogenic microorganisms in an anaerobic biofilter integrated into a biogas reactor. The relevance of the study is обусловлена необхідністю підвищення енергетичної ефективності та стабільності роботи біогазових установок, що переробляють manure-based organic waste, where biomass washout and insufficient microbial retention often limit methane productivity. The proposed model is based on kinetic relationships derived from Monod-type equations and extended to incorporate biomass attachment and growth on carrier surfaces within the biofilter structure. The interaction between substrate loading rate, initial organic matter concentration, hydraulic retention time, and structural parameters of the carrier elements is analytically described. Particular attention is paid to the influence of effective surface area and accumulated active biomass thickness on the methane formation rate. A dynamic representation of the anaerobic digestion process is formulated, enabling quantitative evaluation of changes in biogas production intensity under varying operational conditions. The model demonstrates that increasing the specific surface area of the biofilter and optimizing loading dosage significantly enhances microbial concentration within the reactor, reduces biomass washout, and stabilizes methane yield. The obtained results provide a scientific basis for improving the design and operational control of anaerobic digesters equipped with biofilters. Implementation of the developed modeling approach contributes to increased energy efficiency, higher methane productivity, and improved sustainability of agricultural biogas systems operating within a circular bioeconomy framework.
Mathematical modeling of the process of accumulation of methane-producing microorganisms in an anaerobic biofilter
Keywords: анаеробне зброджування; метаноутворюючі мікроорганізми; біофільтр; математична модель; біогаз; гнойові стоки; інтенсифікація процесу; anaerobic digestion; methanogenic microorganisms; biofilter; mathematical modeling; methane production; biomass retention; process intensification